GAGASAN PENGUJIAN PERATURAN DAERAH KABUPATEN/KOTA TERHADAP PERATURAN DAERAH PROVINSI - Yulianto, Hendra; HB, Gusliana; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In accordance with the principle of state law, any legislation must be sourced and based firmly on the laws and regulations applicable higher level. As an instrument of state law, local regulations are problematic can be tested. Local legislation which contrary to the public interest and / or conflict with higher laws can be tested by two institutions authorized in two models, namely the judicial review by the Supreme Court and executive review by the Government (Home Minister). So, it shows the duality about the rules of local regulation testing that is between the Home Minister and the Supreme Court. Therefore, it needs to be revisited on how the mechanism and who exactly has the authority to examine the local regulation of district/city against provincial local regulation.Keywords: Examination – Local Regulation of District/City – Provincial Local Regulation